Implementasi Model Pembelajaran Kooperatif Tipe Jigsaw dalam Upaya Meningkatkan Motivasi dan Prestasi Belajar Siswa Kelas XI Madrasah Aliyah Swasta Kabupaten Kerinci - Sumarni Sumarni (Unit Pelaksana Teknis Penelitian dan Pengabdian pada Masyarakat (UPT-P4M) STAI Auliaurrasyidin Tembilahan, 2022)
This research is a classroom action research that aims to find and analyze whether implementing the jigsaw type cooperative learning model can increase students' motivation and learning achievement at Madrasah Aliyah Swasta (MAS) Kerinci. The subjects in this study were students of class XI Madrasah Aliyah Private (MAS) Kerinci Regency. Data collection methods used in this study include observation, tests, and documentation. The results showed that through the implementation of the jigsaw type cooperative learning model, students' motivation and learning achievement increased in each cycle. Where in the first cycle was only 52.38%, then increased in the second cycle to 85.71%. Then in the third cycle it increased to 95.24%. This shows that the jigsaw cooperative learning model can increase students' motivation and learning achievement.